Glycinergic and GABAergic Synaptic Activity Differentially Regulate Motoneuron Survival and Skeletal Muscle Innervation - Banks, Glen B. (J Neurosci, 2005)
GABAergic and glycinergic synaptic transmission is proposed to promote the maturation and refinement of the developing CNS. Here we provide morphological and functional evidence that glycinergic and GABAergic synapses control motoneuron development in a region-specific manner during programmed cell death. In gephyrin-deficient mice that lack all postsynaptic glycine receptor and some GABA(A) receptor clusters, there was increased spontaneous respiratory motor activity, reduced respiratory motoneuron survival, and decreased innervation of the diaphragm. In contrast, limb-innervating motoneurons showed decreased spontaneous activity, increased survival, and increased innervation of their target muscles. Both GABA and glycine increased limb-innervating motoneuron activity and decreased respiratory motoneuron activity in wild-type mice, but only glycine responses were abolished in gephyrin-deficient mice. Our results provide genetic evidence that the development of glycinergic and GABAergic synaptic inputs onto motoneurons plays an important role in the survival, axonal branching, and spontaneous activity of motoneurons in developing mammalian embryos.